Education guidelines, frameworks and resources for building virtual care capacity: An integrative review. (April 2023) - Palesy, Debra; Forrest, Gail; Crowley, Margaret E
Introduction: Despite its reported benefits, the accelerated adoption of virtual care since the COVID-19 pandemic has occurred without critical consideration of clinician education and training. This integrative review aims to better understand the necessary education guidelines, frameworks and resources for building the confidence and capability of the workforce for virtual care delivery. Methods: Whittemore and Knafl's (2005) five-stage methodological framework informed this review. Using a clearly articulated search strategy and reporting process, over 8000 pieces of literature were analysed. A final 46 publications comprising 26 scholarly papers and 20 pieces of grey literature were included for review. Results: A set of key curriculum inclusions under three domains: clinical, administrative and technical are proposed. Many publications emphasise a domain-specific approach as the most effective means of translating virtual care knowledge and skills to practice. A number of new domain frameworks have been tailormade for specific disciplines, while well-established frameworks such as the ACGME, CanMEDS, AAMC and IPEC have been adapted for virtual care education. Virtual care checklists, clinical champions and models that involve frontline clinicians, content experts and care recipients are considered useful resources for virtual care education. Discussion: Moving beyond the COVID-19 pandemic, virtual care education for current and future clinicians requires a cohesive, interprofessional approach. This approach should be rigorously evaluated as part of a continuous quality improvement process.